Reciclagem química de Polietileno utilizando Sílica Mesoporosa tipo SBA-15 avalizada por Termogravimetriae Espectrometria de Massas - Fernandes, Glauber José Turolla (2010)
The chemical recycling of polyolefins has been the focus of increasing attention owing potential application as a fuel and as source chemicals. The use of plastic waste contributes to the solution of pollution problems.The use of catalysts can enhance the thermal degradation of synthetic polymers, which may be avaliated by Themogravimetry (TG) and mass spectrometry (MS) combined techniques. This work aims to propose alternatives to the chemistry recycling of low-density polyethylene (LDPE) on mesoporous silica type SBA-15 and AlSBA-15.The mesoporous materials type SBA-15 and AlSBA-15 were synthesized through the hydrothermal method starting from TEOS, pseudobohemite, cloridric acid HCl and water. As structure template was used Pluronic P123. The syntheses were accomplished during the period of three days. The best calcination conditions for removal of the organic template (P123) were optimized by thermal analysis (TG/DTG) and through analyses of Xray diffraction (XRD), infrared spectroscopy (FT-IR), nitrogen adsorption and scanning electron microscopy (SEM) was verified that as much the hydrothermal synthesis method as the calcination by TG were promising for the production of mesoporous materials with high degree of hexagonal ordination. The general analysis of the method of Analog Scan was performed at 10oC/min to 500 oC to avoid deterioration of capillary with very high temperatures. Thus, with the results, we observed signs mass/charge more evident and, using the MID method, was obtained curve of evolution of these signals. The addition of catalysis produced a decrease in temperature of polymer degradation proportional to the acidity of the catalyst. The results showed that the mesoporous materials contributed to the formation of compounds of lower molecular weight and higher value in the process of catalytic degradation of LDPE, representing an alternative to chemical recycling of solid waste